Applying Mixed-Effects Models in Research on Second Language Acquisition: A Tutorial for Beginners - Marc Brysbaert (Languages)
Mixed-effects models have become indispensable tools for analyzing data in second language acquisition (SLA) research. This tutorial offers a step-by-step guide to conducting mixed-effects analyses for simple designs using the gamlj package in jamovi, a user-friendly, free statistical software. We begin by discussing the advantages of mixed-effects modeling over traditional methods, particularly for SLA data, and the rationale for focusing on simple designs. Subsequently, we introduce the gamlj package, highlighting its intuitive interface and error-prevention features. To illustrate the application of the package, we employ toy datasets that can be easily replicated and used with other statistical software. By providing a clear and accessible approach, this tutorial empowers SLA researchers to effectively analyze their data and draw meaningful conclusions.